Comparison of the bleaching efficacy of three different agents used for intracoronal bleaching of discolored primary teeth: An in vitro study - R Ganesh; S Aruna; M Joyson; Manikandan; Deepa (Wolters Kluwer Medknow Publications, 2013)
Everyone wants whiter teeth to make them feel younger and to provide beautiful smiles with the accompanying increase in self-esteem. Bleaching is an established, simple, cost-effective and conservative method for improving the color of the discolored teeth. Aim: The aim of this in vitro study was to compare the bleaching efficacy of 10% carbamide peroxide, 10% hydrogen peroxide and 2g sodium perborate as bleaching agents on the artificially discolored human primary maxillary central incisors. Materials and Methods: Forty extracted human primary central incisors with intact crowns were selected for the study. Pulpectomy was performed and each tooth was artificially stained with 2 ml of fresh human blood and centrifuged. --The teeth were randomly divided into four experimental groups of 10 teeth each and the baseline color evaluation was performed. 0.04 ml of the bleaching agent is syringed into the access cavity of the tooth and, in the control group, 0.04 ml of distilled water was syringed into the access cavity and it was sealed with IRM and placed at 37°C in an incubator throughout the experiment. The color of the bleached teeth was determined at 0, 7 and 14 days. The data obtained were analyzed using ANOVA and Turkey's test. Results: There was statistical significance (P = 0.00) among the carbamide peroxide, sodium perborate, hydrogen peroxide and control groups after 7 and 14 days and a significance of P = 0.013 among the carbamide peroxide, sodium perborate and hydrogen peroxide after two bleaching sessions (day 14) was seen. Conclusions: The bleaching efficacy of 10% hydrogen peroxide gel was more effective than 10% carbamide peroxide and sodium perborate in bleaching the artificially discolored primary teeth.